Doing lines: refrains and copyists in the Cantigas de Santa Maria - Stephen Parkinson (Medievalia)
In the manuscripts of the Cantigas de Santa Maria, the refrains following each strophe, as well as the rubrics preceding each poem, are copied in red ink, into spaces left after the copying of the body of the text in black ink. This creates two specific constraints: the need to fit text into predetermined spaces, and the repetition inherent in copying the same text many times over. The task was probably delegated to junior copyists, meaning that many pages have more than one hand represented. Close study of the copying of refrains reveals that the copyists used a range of devices to vary and justify the text of refrains, and that copying could proceed across the whole page rather than column by column.